Sebastian Prixner (1771‒1855) as a Music Theory Teacher - Lewandowski, Stephan (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2023)
Till present day only very few writings are existing on Sebastian OSB Prixner (actually Peter Prixner). In 1789 a teaching book by Prixner was published, which is entitled Kann man nicht in zwei, oder drei Monaten die Orgel gut, und regelmäßig schlagen lernen? Mit Ja beantwortet und dargethan vermittelst einer Einleitung zum Generalbasse. This relatively comprehensive writing with probably one of the most enthusiastic and promising titles in the history of music theory is of some interest, as it contains several rules and graphic depictions that are specially designed for beginners in figured bass, for example tables of all dissonances both in major and minor mode, a table which explains and summarizes the intervals not usually indicated in figured bass signatures, or an abstract graph of the rule of the octave without any notes, but only with figured bass indications. The author calls the rule of the octave “Oktavsystem” and traces it back to the theories of Jean-Philipp Rameau (1683–1764) and François Campion (1686–1747). Even though it might be questionable, if the book ever reached its aim and taught playing the organ to musical beginners in only maximum twelve weeks, it bears some potential for a practical oriented and historically informed education in music theory today, especially in the context of the raising discipline of applied piano praxis. In the article is shown this potential by mainly concentrating on the third part of the book, a main section of Prixner’s writing that deals with explanations about how to improvise—that means: how to invent free fantasies as well as how to prelude—on the organ. Both the author’s partially inventive ways of explaining complex interrelationships to beginners and his refreshing, at times humorous writing style might still be motivating for present day students.